Teaching Literacy in First-Grade of Primary School During COVID-19 Pandemic - Mehmet Bozan; Hüseyin Anılan (Universitas Pendidikan Indonesia, 2022)
Along with the COVID-19 pandemic, a new era had to be passed in education. The education process in Turkey has been maintained entirely or partially in the form of remote or distance education, or partly face-to-face since the outbreak in the process of being face-to-face education opportunities. This research seeks to examine in-depth how literacy teaching in the first grade, one of the essential processes of primary school education, took place during the pandemic. The research applied a case study, one of the qualitative research methods. In addition, the participants in this research were determined based on criterion sampling. The data were collected using semi-structured interviews with teachers and parents of students and the observations made by one of the researchers in online lessons. The data obtained were analyzed through content analysis. The findings are presented under the themes of